SEPUTAR KONFLIK BENDA CAGAR BUDAYA: Saat Sangiran Dalam Sengketa - Saptaningrum, lrna (Naditira Widya, 2009)
Conflict is potent to happen anywhere including' occurrences involving cultural heritages, among others is Sangiran, which has been acknowledged as the world's heritage. Sangiran provides data on ancient human and animal and culture which was once existed around 1. 8 million years ago. The conflict on Sangiran has been based on the differences of perception between stakeholders to manage Sangiran as an archaeological resource, for instance how to deal with and signify its potent characteristic, importance and its existence as the world's heritage in Indonesia. In regard to conflict management context, I analyzed this case by using the 'onion analogy'. By employing this approach, the root of conflict was mapped to extract a number of alternative solutions and chose the one which accommodate the interest of each party. This article discusses the conflict on Sangiran as a case study about conflict management in a cultural resourch management system.